Design of Table and Chairs for Packaging Tempe Chips Work Station for Reducing the Risk of Occupational Diseases in Putra Tunggal Home Industry Wonosobo - Faqih, Ahmad Saifulloh; Mulyati, Guntarti Tatik; Wagiman, Wagiman (Agroindustrial Journal, 2024)
Home Industry Putra Tunggal Wonosobo is a tempeh chip industry whose production process is manual, so it can have a negative impact on worker ergonomics. Preliminary research was conducted by interviewing pain complaints and assessing work posture using the OWAS method. The tempeh chips packaging workstation was the workstation that had the most pain complaints at 67.86% (19 of 28 body parts) and the highest OWAS score at 4, so this was at high risk of experiencing musculoskeletal disorders. The next study used the NBM questionnaire to analyze the level of pain due to work and RULA for work posture. CATIA software was used to design tables and chairs, as well as assess the posture of the design results using the RULA method. Worker performance will be compared before and after using tables and chairs based on the level of body pain due to work (NBM) and work posture (RULA). The research results showed a decrease in the risk of work-related diseases by 80 and 78 to 40 and 44 (from high to low-risk levels) as well as a decrease in the RULA score from 7 (dangerous posture) to 2 (good posture).